Narrativas de um "milagre": as transformações bioculturais no Cerrado brasileiro (Revista de História Regional, 2020)
This article aims to address how the Cerrado has become the privileged territory for the expansion of the agricultural frontier in Brazil. Until World War II, considered a territory dominated by acid soils and at most suitable for pasture, the impulse of the Brazilian State and private companies in research on soil fertility transformed the Brazilian Cerrado into a "grain barn" and modern cattle-raising in little more than four decades – a "miracle”, in the words of agribusiness advocates. On the other hand, many of the traditional fertilization and cultivation practices have been relegated. For this research, bibliographic references and archive research were used, mainly related to soil research.